A STUDY ON THE CURRENT KBP RULES OF PROCEDURE IN HANDLING COMPLAINTS AS PERCEIVED BY SELECTED METRO MANILA RADIO STATIONS. - 4 0 16; 5 (2010)
A Study on the Current KBP Rules of Procedure in Handling Complaints as Perceived by Selected Metro Manila Radio Stations delved into the perception of radio stations such as, DZMM, DZXL and DZRH for AM radio stations and 90.7 Love Radio, 101.1 Yes! FM and Tambayan 101.9 for FM radio stations. The thesis analyzed the KBP's method of handling complaints through the Resolution of Complaints Procedure. Kapisanan ng mga Brodkaster ng Pilipinas (KBP) is a private organization that advances and sustains the highest standards of quality in the broadcast industry through the exercise of self-regulation for responsible broadcasting. It advocates positive changes by upholding the social, cultural and economic development of the nation. On the other hand, KBP Standards Authority established the KBP Rules of Procedures in the Resolution of Complaints and the Broadcast Code together with its equivalent penalties if violated. The KBP-SA's complaints resolution was revised in 2004 that dictates the procedures that KBP needs to do whenever there is a complaint being filed. The thesis made use of a survey interview questionnaire that was submitted to the different radio stations around Metro Manila, and were answered by the station representatives respectively. The questionnaire contains questions Current KBP Rules of Procedure in Handling Complaints... 4 about the awareness and understanding of each radio stations on the KBP's rules of procedure of handling complaints, and the effectiveness of this procedure. The data gathered showed that KBP has lack of awareness and information campaign in making their members knowledgeable about their rules and procedures in handling complaints. Most of the respondents of this study are aware of the KBP's rules of procedure in handling complaints but does not completely understood what it means and how it is being executed. Despite the distribution of the KBP's rules of procedure in handling complaints, it is not enough that the broadcasters and managers have copies of the said procedure for them to have a full grasp of its contents. The respondents of the study do not seem to have any problems with the current KBP's rules of procedure their problems are more likely on the dissemination of it. KBP, as a non-profit private organization with minimal funding has lack of monitoring procedures to fully implement their broadcast code. Feedback mechanism makes the monitoring functions of KBP alive. The researchers came up with recommendations that might be used for future resources: KBP-SA must have a clearer set of flowchart on the KBP's rules of procedure in handling complaints; KBP should explain further the contents on how they handle complaints filed by concerned listeners; KBP should make sure that each of their members has completely read and understood the KBP's rules of procedure in handling complaints.
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila 2010.;Bachelor of Mass Communication.
Keywords: 2 -- 0; 6; 20; 20; 2